The silent child : communication without words - Magagna, Jeanne, ....-; Scott, Michelle, ....- (London : Karnac, 2012)
The Silent Child: Communication without Words describes a way of understanding and communicating with children who are not speaking, but rather using their bodies and somatic symptoms to express states of mind. Jeanne Magagna has worked for 45 years trying to find ways of helping these children, varying in age and symptoms. Using infant observation methods of understanding primitive states of mind expressed through gestures of eyes, hands, body posture, she has worked in in-patient or out-patient settings with contributors: a group of psychiatrists, psychologists, family and child psychotherapists, physiotherapists, nurses, therapeutic care workers, teachers, parents' groups and work discussion seminar members in out-patient and in-patient settings. In their chapters, the professionals and a parent show how they use their observation, empathy and countertransference experiences to promote understanding in the silent child and his/her parents and siblings.
Young children -- Young people -- Creative activities for non-speaking children.
Includes bibliographical references and index.
Keywords: Communicatie -- Kinderen; Communicative disorders in children; Mutism; Mutisme